PENGARUH MOTIVASI DAN LINGKUNGAN KELUARGA TERHADAP KINERJA BELAJAR SISWA SMP SEJAHTERA TANJUNGBINTANG LAMPUNG SELATAN - Victor Marindra A (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2010)
Teaching and learning process is a human process that demands the involvement ofchildren as individuals then the success of this process requires an open attitude towards theenvironment and willing to cooperate with each other. This process also will mature the childprecisely because there is no educational process that requires close contact with minors such asthe learning process, specifically in primary and secondary schools.Research from the author specializing in motivation and the influence of family environmenton the performance of junior high students learn Prosperous. Objectives to be achieved in this studyis analyzing whether the motivation of students and family environment, simultaneously or partialeffect on the learning performance of junior high students Prosperous Tanjungbintang. The results ofhypothesis testing showed physical family environment variables have regression coefficients of thelargest or most dominant of the variables studied.